Body Temperature and Heart Rate Monitoring System Using Fuzzy Classification Method - M. Yayan Nurhadiansyah; Rahardhita Widyatra Sudibyo; Moch. Zen Samsono Hadi (International Journal of Artificial Intelligence & Robotics (IJAIR), 2022)
Climbing becomes one of the extreme sports that test endurance with nature, just like in a mountainous environment. In addition to the excitement and fun that climbing provides, climbers enjoy the opportunity to view breathtaking natural scenery and breathe in the fresh air drawn directly from the surrounding environment. Because of the temperature in the cold mountains, there are frequent and common obstacles Not realized by the climbers, such as hypothermia. Hypothermia is a condition in which the body temperature drops below 35oC. When body temperature is below normal 37oC, nervous system function and other body organs will experience interference. If not soon Left untreated, hypothermia can lead to heart failure, disturbances respiratory system, and even death. To anticipate things requires a system that functions to know the condition of mountaineer health. The system to be created uses the Mamdani fuzzy logic method, which decides whether the climber is healthy. The fuzzy logic method is used for decision-making based on body temperature and heart rate values. Implementation of the system in the form of a prototype containing sensors and mini-computers located at the climbing post, with data transmission using a node sent from post x to the main post to be uploaded to the database so that it can be known by the admin or rescue team when climbers need help in critical situations. This is done so that the condition can be monitored.